Idiopathic and secondary restless legs syndrome during pregnancy in Japan: Prevalence, clinical features and delivery-related outcomes. - Chikara Yoshimura (Public Library of Science (PLoS), 2021)
Objective The aim of this study was to investigate prevalence of idiopathic and secondary restless legs syndrome (RLS) according to pregnancy trimester, and its effects on delivery-related outcomes among pregnant women in Japan. Methods This was a single-center, prospective observational study. One hundred eighty-two consecutive pregnant women participated in the study from June 2014 to March 2016. Participants were interviewed and examined in the second and third trimesters of pregnancy and 1 month after delivery. At each term, RLS was identified by a research assistant and then specialist in sleep medicine based on the diagnostic criteria of the International Restless Legs Syndrome Study Group. Delivery-related data was collected from medical charts. RLS was classified as idiopathic RLS, which originally existed before the index pregnancy, or secondary RLS, which newly appeared during the index pregnancy. Results The prevalence of RLS was 4.9% (idiopathic 3.3%, secondary 1.6%) in the second trimester, 5.0% (idiopathic 0.0%, secondary 5.0%) in the third trimester, and 0.6% (idiopathic 0.0%, secondary 0.6%) after delivery. Prolonged labor, emergency Cesarean section, and arrest of labor tended to be more frequent in idiopathic and/or second RLS (all p<0.05). Conclusions The prevalence of RLS during pregnancy was 4-5% and decreases after delivery in current Japan. The presence of RLS was associated with an increase in some delivery-related outcomes. Early detection and treatment of RLS during pregnancy may be beneficial to safe delivery for pregnant women.